BENTUK DAN GAYA PENUTURAN FILM DOKUMENTER BERBASIS BUDAYA DAERAH PB XII: BERJUANG UNTUK SEBUAH EKSISTENSI KARYA IGP. WIRANEGARA - Candra, Nur Rahmat Ardi (Acintya, 2015)
This research entitled â€œBentuk Dan Gaya Penuturan Film Dokumenter berbasis Budaya Daerah;Â PBXII: Berjuang Untuk Sebuah Eksistensi, Karya IGP. Wiranegaraâ€ (The Form And Style of SpeechÂ in Documentary Film Based On The Local Culture; PBXII: Fighting For An Existence, by IGP.Â Wiranegara). The research aims to describe the form and style of speech as well as the dramatic plotÂ of the film. IGP Wiranegara, through the documentary film, tries to present the outstanding form andÂ style in conveying the theme of the film. The film is told dramatically by giving the point of view ofÂ strong character through the description of Paku Buwana XII. In the film, Paku Buwana XII is described to try hard in order that Surakarta Palace continuously exists as part of the Central JavaÂ cultures, especially Surakarta (Solo).Keywords: form, style, documentary film, local culture.